Support for the location of negative posttraumatic cognitions in the diagnosis of posttraumatic stress disorder. (February 2015) - Hiskey, S.; Ayres, R.; Andrews, L.; Troop, N.
Highlights: Support is provided for the placement of posttraumatic cognitions within DSM-5 PTSD. A large, diverse, sample of participants provided data for the study. These results apply to a range of traumatic events. Abstract: Objective: To investigate the extent to which negative posttraumatic cognitions predict, and so can be best located within, the DSM-5 (APA, 2013) individual symptom clusters of posttraumatic stress disorder (PTSD). Method: An online survey of traumatic experiences, featuring 528 adults. Results: Negative posttraumatic cognitions seem best placed within the Numbing/Detachment symptom cluster. Negative posttraumatic cognitions relating to the self predict higher levels of symptoms across the clusters. While negative cognitions relating to the world contributed to most symptom groups, self-blame cognitions did not. Conclusions: Our findings support the placement of posttraumatic cognitions as part of the Numbing/Detachment symptom cluster within the DSM-5rather than the Intrusion, Avoidance and Hyperarousal clusters.